Penilaian Risiko Postur Kerja dengan Metode Rapid Upper Limb Assessment Pemasangan Part Clip dan Wiring pada Proses Perakitan Dump Truck di PT XYZ Politeknik STMI Jakarta - Irma Agustiningsih Imdam; Dianasanti Salati; Nadhif Rahmawan; Yanuar Angkasa Artanto; Lintang Linuwih; Widiyana (Jurnal Industri dan Teknologi Samawa, 2025)
The process of installing clips and wiring on the dump truck assembly line with an uncomfortable working posture of the operator, so that complaints due to fatigue often occur. This is because at the time of installation the part the operator has to bend because it is blocked by the battery. This study aims to assess the operator's work posture during the process of installing the clips and wiring, so that the risks obtained due to fatigue due to work can be known. The method used in this study is the Rapid Upper Limb Assessment (RULA) method. This method begins by distributing the Nordic Body Map (NBM) questionnaire to find out which parts of the body feel pain and fatigue. Based on the measurement results, the angle of the upper arm is 450 – 900 with a score value = 3, the lower arm is formed with an angle of 00 – 600 with a score = 2, the wrist part forms an angle of >150 with a score = 2. The results of the RULA table assessment based on the angles formed for each section, namely part A score=7, part B score 11, and part C score as end=7 are included in the high risk. Recommendations that can be given for high risk are observation and application of remedies.